2022
DOI: 10.1186/s12902-022-01172-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between triglyceride–glucose index and nonalcoholic fatty liver disease in type 2 diabetes mellitus

Abstract: Background Lipid and glucose metabolism abnormalities are associated with nonalcoholic fatty liver disease (NAFLD). The triglyceride–glucose (TyG) index is a recently developed indicator that can identify individuals at risk for NAFLD. However, the applicability of the TyG index for identifying NAFLD in patients with type 2 diabetes mellitus (T2DM) is unclear. The aim of this study was to investigate the ability of the TyG index to identify individuals at risk for NAFLD in the T2DM population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…However, no evidence has been published regarding the relationship between TyG-WHTR and prediabetes in normal-weight individuals. However, in recently published studies, TyG-WHTR exceeded the commonly used anthropometric markers in predicting diabetes ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, no evidence has been published regarding the relationship between TyG-WHTR and prediabetes in normal-weight individuals. However, in recently published studies, TyG-WHTR exceeded the commonly used anthropometric markers in predicting diabetes ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 93%
“…However, no evidence has been published regarding the relationship between TyG-WHTR and prediabetes in normal-weight individuals. However, in recently published studies, TyG-WHTR exceeded the commonly used anthropometric markers in predicting diabetes (45,46). The TyG-WHTR index's capacity to detect prediabetes was contrasted with FPG's to determine whether it could be a useful screening tool.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al. investigated the association between the TyG index and NAFLD and demonstrated that the OR for NAFLD associated with the TyG index was significantly higher in females than males (females: OR 2.69, 95% CI 1.67–4.23; males: OR 2.09, 95% CI 1.59–2.76) ( 29 ). In another study that investigated a possible dose-response association between the TyG index and the risk of NAFLD, the TyG index had a stronger association with NAFLD in females than in males (females: OR 4.80, 95% CI 3.90–5.90; males: OR 2.97, 95% CI 2.55–3.46) ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…(BMI <24kg/m^2,OR:1.010, 95% CI:1.008, 1.013)than those with higher BMI(24kg/m^2≤BMI<28kg/ m^2,OR:1.005,95%CI:1.003,1.007;BMI≥28,OR:1.004,95%CI:0.999, 1.009). Some studies suggest that the relationship between TyG index and NAFLD risk is significantly stronger in non-obese subjects than in obese subjects (13,32). It is unclear how BMI influences TyG-WC and NAFLD, but it may be related to relatively lean people's significantly reduced skeletal muscle mass.…”
Section: Discussionmentioning
confidence: 99%